Multiple response optimisation: An approach from multiobjective stochastic programming - Díaz-García, José A.; Bashiri, Mahdi (Applied mathematical modelling, 2014)
The multiresponse surface problem is modelled as a multiobjective stochastic optimisation, and diverse solutions are proposed. There are several crucial differences highlighted between this approach and the other proposed solutions. Finally, some particular solutions are applied and described in detail in a numerical example.